Valsartan Blocked Alcohol‐Induced, Toll‐Like Receptor 2 Signaling‐Mediated Inflammation in Human Vascular Endothelial Cells. (October 2014) - Wang, Yushu; Li, Yi; Shen, Qingyu; Li, Xiangpen; Lu, Juan; Li, Xiangping; Yin, Deling; Peng, Ying
<x xml:space="preserve">Abstract</x> Background Alcohol consumption induces inflammatory damage in vessels, and the underlying mechanism is unclear. Valsartan, as one of the angiotensin receptor blockers (ARBs), plays a role in the inhibition of inflammatory reactions in vascular dysfunction. This study is to investigate the role of Toll‐like receptor 2 (TLR2) in alcohol‐induced inflammatory damage in vascular endothelial cells in vitro and to explore the protective effect of valsartan on alcohol‐induced and TLR2‐mediated inflammatory damage. Methods The human umbilical vein cell line (EA.hy926) were exposed to alcohol at 0 to 80 mM for 0 to 48 hours with or without valsartan pretreatment. The expression of TLR2 signaling, including TLR2, tumor necrosis factor receptor associated factor 6 (TRAF‐6) and nuclear factor kappa B (NF‐κB) p65 were detected by Western blot. The levels of proinflammatory cytokines, tumor necrosis factor‐α (TNF‐α) and interleukin‐6 (IL‐6), were determined by ELISA. To confirm the role of TLR2, we functionally up‐regulated or down‐regulated TLR2 by using TLR2 agonist or TLR2 small interfering RNA (siRNA), respectively. To further investigate the mechanism of alcohol on renin‐angiotensin system, we detected the expression of angiotensin II receptor type 1 (AGTR1) in protein levels. Results The expression of TLR2, TRAF‐6, NF‐κB p65, and the proinflammatory cytokines, TNF‐α and IL‐6, were significantly increased after alcohol exposure in EA.hy926 endothelial cells. This was enhanced by TLR2 agonist, and was inhibited by TLR2 siRNA transfection. The pretreatment of valsartan resulted in an inhibition of TLR2 signaling and proinflammatory cytokines. The expression of AGTR1 was up‐regulated after alcohol exposure, and was blocked by valsartan pretreatment. Conclusions TLR2 signaling‐mediated alcohol induced inflammatory response in human vascular epithelial cells in vitro, which was inhibited by valsartan.